African economic development - Hance, William Adams; Council on Foreign Relations (London: published for the Council on Foreign Relations by Pall Mall P., 1967)
This book originated as research papers for the Council on Foreign Relations and Economic Development of Africa
Maps on endpapers.
Bibliography: p. 303-309.
oo 23/08/2018
Loans
Keywords: Africa